THE HARMONY OF TUYUK AND TAJNIS IN THE CREATIVE WORK OF ZAHIRIDDIN MUHAMMAD BOBUR ("Conference on Universal Science Research 2023", 2026)
This article analyzes the use of the tajnis (paronomasia) literary device in the tuyuks of Zahiriddin Muhammad Bobur. Through the examples of “Chindurur”, “Qoysorig‘a”, “Yuz ila”, “Taning”, and “Davlat tog‘i”, the poet’s mastery in creating multiple layers of meaning through wordplay is revealed. The study highlights the significant role of tajnis in enhancing the artistic and aesthetic value of Bobur’s poetry.